Pembuatan Hand Sanitizer dan Promosi Kesehatan dalam Pengendalian Covid-19 di Ma’had Al Atsar Qur’anic - Dewi Yuniasih; Suhendra Suhendra; Nuni Ihsana; Mar’atu Roisa Amini; Faiyana Nurul Arrifqi; Saumi Syahri Finanda; Tri Aulia Aflah (Jurnal Pengabdian Masyarakat (abdira), 2021)
Religious activities at the taklim assembly, several local Islamic boarding schools and al-quran education parks managed collectively by residents are still running face-to-face activities (offline). The desire to organize religious education as a moral foundation for future generations by preventing the spread of COVID-19 is a dilemma. Therefore, activities are needed to promote health protocols and their implementation to support the conditions of a healthy religious learning process in these places. The main purpose of this service is to provide an understanding of health promotion in the prevention and control of Covid-19 and provide training on the manufacture and use of sanitation materials to partners. Methods for implementing community service activities include contact and discussion with partners, preparation of health promotion tools and media, preparation and purchase of tools and materials for making hand sanitizers as well as FGD discussions related to activities. The result of this activity is an increase in understanding and application of health promotion regarding the prevention and control of the spread of Covid-19, both in the mosque environment, religious study rooms and around mosques.